Changing consumption patterns: implications on food and water demand in India - Amarasinghe, Upali A.; Shah, Tushaar; Singh, Om Prakash (International Water Management Institute, 2007)
Increasing income and urbanization are triggering a rapid change in food consumption patterns in India. This report assesses India's changing food consumption patterns and their implications on future food and water demand. According to the projections made in this study, the total calorie supply would continue to increase, but the dominance of food grains in the consumption basket is likely to decrease by 2050, and the consumption of non-grain crops and animal products would increase to provide a major part of the daily calorie supply. Although the total food grain demand will decrease, the total grain demand is likely to increase with the increasing feed demand for the livestock. The implications of the changing consumption patterns are assessed through consumptive water use (CWU) under the assumptions of full or partial food self-sufficiency.